ATTRITION OF DEMOCRACY OR HARMONY OF LEGACY: Local Wisdom Study of the Gibran Rakabumi Raka Political Dynasty - Mustaqim, Andika Hendra (IAIN Ambon, 2023)
This research aims to explore local wisdom in the phenomenon of political dynasties on social media in the figure of the Mayor of Solo, Gibran Rakabuming. Using a qualitative approach and psychological narrative analysis method, this research analyzes videos on Gibran's YouTube account. This research found Gibran's political dynasty motives, such as continuing the political leadership initiated by his father, utilizing primordial cultural support and patronage, maintaining his father's legacy of leadership, and building a political career for the future. Gibran's political dynasty strategy is to use family characteristics; using Javanese and Islamic traditions as tools, and adapting to developments in time and technology. Regarding the impact of political dynasties on Gibran, this research reveals wisdom in politics, building identity, showing oneself as a quality leader; and political dynasties do not destroy democracy, and show that political dynasties provide progress in various sectors.